DOP15 Intestinal ultrasound correlates with colonoscopy and biomarkers, and can be used in a tight monitoring approach to assess response to therapy in Crohn's disease: a multicentre prospective study. (30th January 2023) - Morão, B; Revés, J; Nascimento, C; Frias Gomes, C; Cúrdia Gonçalves, T; Freitas, M; Castro, F; Moreira, M J; Cotter, J; Pereira, F; Caldeira, A; Sousa, R; et al.
Abstract: Background: Intestinal ultrasound (IUS) is a non-invasive monitoring tool increasingly being used to assess response to therapy in Crohn's disease (CD). Herein we describe the longitudinal evolution of IUS parameters, and its correlation with clinical, laboratorial and endoscopic parameters during the first year of infliximab (IFX) therapy. Methods: Prospective multicentre cohort study of patients with active CD starting IFX. Harvey-Bradshaw index (HBI), C-reactive protein (CRP), fecal calprotectin (FC) and IUS were performed at week (W) 0, 14, 30 and 54. Ileocolonoscopy was performed at W0 and W54. IFX through levels (ITL) were measured at W14, 30 and 54. Clinical remission (CR) was defined as HBI<5 and laboratorial remission (LR) as CRP <0.5mg/dL and FC <150ug/g. IUS response was defined as a reduction >25% in bowel wall thickness (BWT) and IUS remission as normalization of BWT (≤3mm), color doppler sign (CDS≤1), wall stratification and inflammatory fat. The IBUS-SAS score was used to assess disease activity and includes BWT, doppler sign, stratification and inflammatory fat. Endoscopic response was defined as 50% reduction of SES-CD in most affected segment and endoscopic healing as total SES-CD <3. Results: 62 patients with CD (50% male; mean age 36±15y) were included: all with IUS at W0 and W14, 58 (94%) patients with IUS at W30 and 53 (85%) at W54. Following therapy initiation there was a positive evolution of all assessed parameters; IUS response and remission increased gradually from baseline to week 54 (Table 1 and Figure 1). Figure 2 illustrates the reduction of BWT and IBUS-SAS score from baseline to week 54. The reduction of BWT and IBUS-SAS were significantly more pronounced in the first 14 weeks of therapy (BWT: DW0-14 vs DW14-30, p=0.015; IBUS-SAS: DW0-14 vs DW14-30, p=0.004; DW0-14 vs DW30-54, p=0.037). There was a good agreement between IUS and colonoscopy for evaluation of the most affected segment at baseline (kappa 0.788, p<0.001). In all time points, there was a significantly fair to moderate correlation between ultrasonographic parameters (BWT, CDS and IBUS-SAS score) and laboratorial biomarkers (specially fecal calprotectin) (Table 2). After induction (week 14), there were also a fair correlation between IBUS-SAS and ITL (r=-0.277, p=0.034). Conclusion: We found a significantly fair to moderate correlation between IUS parameters and laboratorial and endoscopic parameters during the first year of infliximab therapy. BWT and IBUS-SAS score reduction was more pronounced during induction therapy. IUS can be reliably used to monitor disease activity longitudinally, in a tight monitoring strategy.